A supramolecular hydrogel based on carbamazepine. Issue 83 (4th September 2015) - Zhou, Ying; Cui, Hongjing; Shu, Chang; Ling, Ya; Wang, Ran; Li, Hongmei; Chen, Yadong; Lu, Tao; Zhong, Wenying
Abstract : In this communication we report the first supramolecular hydrogel based on an antiepileptic drug carbamazepine (CBZ). CBZ plays a dual role of a drug molecule and an aromatic capping group in this self-delivery system. Abstract : In this communication we report the first supramolecular hydrogel based on an antiepileptic drug carbamazepine (CBZ). CBZ plays the dual role of a drug molecule and an aromatic capping group in this self-delivery system.